Does the foliage of Acacia spp. determine their distribution? : a study to determine how two different leaf forms may alter the distribution of Acacia spp. in relation to phosphorus concentration, mean annual precipitation and temperature within Australia and South Africa - Cyrus, Mark (Department of Biological Sciences, 2017)
The genus Acacia consists of over 1000 species, of which most are native to Australia. An intriguing aspect of this genus is their divergence into two major groups that poses entirely different leaf structures. The ﬁrst of these groups consist of Acacias have fern like bi-pinnate leaves, that are subdivided into small leaﬂets. The other group posses' what are known as phyllodes which are also called 'simple leaves'. The evolution of phyllodes within the genus Acacia seems to have been localized, occurring largely within Australia. Many hypotheses have been put forward in the past to try and explain what advantages phyllodes incur on the species that bear them. Many studies have indicated drought tolerance and resistance as a main evolutionary driver of phyllodes. However due to the very low concentrations of nutrients particularly P within Australia and the generally longer life span exhibited by phyllodes compared to normal compound leaves, we hypothesized that phyllodes were in fact an adaptation to nutrient limitation, and provide a way in which to limit nutrient loss back to the environment. In order to test our hypothesis, we analysed the distributions of 6 Acacia spp., three of which were phyllodinous and three of which bore compound leaves, in relation to soil P concentrations, mean annual precipitation and temperature. Due to all 6 of these species being invasive within South Africa we compared their distribution of these species both within Australia and South Africa to determine wither species were following similar trends. In this study we determined that phyllodinous Acacia spp. were occurring on low P soils at signiﬁcantly higher frequencies to species bearing compound leaves. The reverse relationship however was also recorded for areas of high P with compound leaf bearing species being more dominant. Species followed similar trends between continents, however due to these species being invasive in SA it was assumed that species had not reach their ideal or potential distribution ranges which may mean that trends may become stronger with time. Temperature and rainfall did not show any relationship to foliage type and it was there for concluded that phosphorus concentrations have been the main evolutionary driver of the phyllode.